One dimensional man - Marcuse, Herbert (London, 1968)
Originally published in 1964, One-Dimensional Man quickly became one of the most important texts in the ensuing decade of radical political change. This second edition, newly introduced by Marcuse scholar Douglas Kellner, presents Marcuse's best-selling work to another generation of readers in the context of contemporary events.
Keywords: Sociology